1999
DOI: 10.1017/s0074180900203884
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Histories of Dwarf Galaxies in the Local Group

Abstract: The star formation histories of Local Group (LG) dwarf galaxies and more distant potential LG members are reviewed. Problems in defining the spatial extent of the LG and membership are briefly discussed. The morphological types found in the LG are presented, and it is suggested that we see continuous evolution from low-mass dwarf irregulars (dIrrs) to dwarf spheroidal galaxies (dSph) in the LG.Star formation histories for LG dwarfs and nearby LG candidates are compiled using population boxes. No two dwarfs, ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 109 publications
3
37
0
Order By: Relevance
“…Other metallicity indicators include the colour and morphology of the horizontal branch (HB) in the CMD (Grebel 1998), although this cannot be uniquely translated into metallicities due to poorly understood "second parameter effects", also known from the study of HBs in globular clusters. Intermediate in character between photometric and spectroscopic abundance determinations is the fraction of carbon (C) stars among the late type giants, and the number of carbon rich (WC) to nitrogen rich (WN) Wolf-Rayet (WR) stars.…”
Section: Photometry Of Resolved Stellar Populationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Other metallicity indicators include the colour and morphology of the horizontal branch (HB) in the CMD (Grebel 1998), although this cannot be uniquely translated into metallicities due to poorly understood "second parameter effects", also known from the study of HBs in globular clusters. Intermediate in character between photometric and spectroscopic abundance determinations is the fraction of carbon (C) stars among the late type giants, and the number of carbon rich (WC) to nitrogen rich (WN) Wolf-Rayet (WR) stars.…”
Section: Photometry Of Resolved Stellar Populationsmentioning
confidence: 99%
“…It is not our intent here to give a general description of the Local Group dwarfs, recent and excellent reviews can be found in e.g. Mateo (1998, which also contains a compilation of very useful data) and Grebel (1998); see also the book "Stellar astrophysics for the Local Group" (eds. Aparicio et al 1998) and the proceedings of the recent IAU symposium "The Stellar Content of Local Group Galaxies" (eds.…”
Section: The General Properties Of Metal-poor Galaxiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The latter, in particular, explains naturally why most dSphs in the Local Group (where they are best studied given their low luminosity) are at present satellites of the Milky Way or Andromeda galaxies (van den Bergh 1994;Grebel 1999;Mateo 2008). Tidal stirring, however, fails to explain the origin of isolated dSphs such as Cetus (or Tucana), whose large distance from any major galaxy excludes repeated tides as the main mechanism driving its morphology, or its transformation.…”
Section: Introductionmentioning
confidence: 99%